From referendum to secession – The Québécois process of accession to sovereignty and its teachings with respect to self-determination - Guénette, Dave; Gagnon, Alain-G. (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
As a result of the two referenda on sovereignty held in 1980 and 1995, Quebec has somehow become something of a figurehead for western democracies. It represents a modern developed state seeking national independence, not in time of war or because of serious political oppression, or to end colonial dependence in its territory or rid itself of an antidemocratic political system, but rather and above all by taking this path for cultural, identity, linguistic and economic reasons. In this regard, and notwithstanding the fact that both referenda failed to bring independence, it is still fair to grant the Québéquois nation a pioneering role in terms of recognising the right of minority nations to secede. In adopting this approach, this article looks at the Québéquois process of accessing sovereignty and the lessons that it can offer, in this regard, to a multinational Spain.
Keywords: External self-determination; minority nations; secession; referendum; Quebec; Catalan sovereignty process